MicroRNA as a promising molecular biomarker in the diagnosis of breast cancer - Miranda, Felipe Silva de; Slaibi-Filho, José; Calasans dos Santos, Gabriel; Carmo, Nathalia Teixeira; Kaneto, Carla Martins; Borin, Thaiz Ferraz; Luiz, Wilson Barros; Gastalho Campos, Luciene Cristina (Frontiers in Molecular Biosciences, 2024)
Breast cancer represents the most prevalent malignancy among women. Recent advancements in translational research have focused on the identification of novel biomarkers capable of providing valuable insights into patient outcomes. Furthermore, comprehensive investigations aimed at discovering novel miRNAs, unraveling their biological functions, and deciphering their target genes have significantly contributed to our understanding of the roles miRNAs play in tumorigenesis. Consequently, these investigations have facilitated the way for the development of miRNA-based approaches for breast cancer prognosis, diagnosis, and treatment. However, conducting a more extensive array of studies, particularly among diverse ethnic groups, is imperative to expand the scope of research and validate the significance of miRNAs. This study aimed to assess the expression patterns of circulating miRNAs in plasma as a prospective biomarker for breast cancer patients within a population primarily consisting of individuals from Black, Indigenous, and People of Color (BIPOC) communities. We evaluated 49 patients with breast cancer compared to 44 healthy women. All miRNAs analyzed in the plasma of patients with breast cancer were downregulated. ROC curve analysis of miR-21 (AUC= 0.798, 95% CI: 0.682 -0.914, p<0.0001), miR-1 (AUC= 0.742, 95% CI: 0.576 -0.909, p=0.004), miR-16 (AUC=0.721, 95% CI: 0.581 -0.861, p= 0.002) and miR-195 (AUC= 0.672, 95% CI: 0.553 -0.792, p=0.004) showed better diagnostic accuracy in discrimination of breast cancer patients in comparison with healthy women. miR-210, miR-21 showed the highest specificities values (97.3 %, 94.1 %, respectively). Following, miR-10b and miR-195 showed the highest sensitivity values (89.3 %, and 77.8 %, respectively). The panel with a combination of four miRNAs (miR-195 + miR-210 + miR-21 + miR-16) had an AUC of 0.898 (0.765-0.970), a sensitivity of 71.4 %, and a specificity of 100.0 %. Collectively, our results highlight the miRNA combination in panels drastically improves the results and showed high accuracy for the diagnosis of breast cancer displaying good sensitivity and specificity.